2014
DOI: 10.2340/00015555-1644
|View full text |Cite
|
Sign up to set email alerts
|

A Segmental Rash in a Young Male: A Quiz

Abstract: A 16-year-old student presented with a 4-year history of an occasionally itchy rash on his right shoulder. He subsequently developed a similar eruption on the right submental region. He was otherwise healthy with no systemic symptoms. On examination, a large segmental area of non-scaly hyperpigmented macules on the anterior shoulder extending to the chest was seen (Fig. 1A). An erythematous inflammatory plaque was seen on the submental region (Fig. 1B).A punch biopsy was taken from both areas. The appearances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…In addition, our patient did not have any history of trauma. Only a few cases have been reported that skin lesions are confined to a particular segment or area of the body, described as nevoid, linear, or unilateral …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our patient did not have any history of trauma. Only a few cases have been reported that skin lesions are confined to a particular segment or area of the body, described as nevoid, linear, or unilateral …”
Section: Discussionmentioning
confidence: 99%
“…Only a few cases have been reported that skin lesions are confined to a particular segment or area of the body, described as nevoid, linear, or unilateral. 3,4 The pathogenesis of spontaneous localized MPCM has not been fully elucidated, although some explanations have been proposed.…”
Section: Case Reportmentioning
confidence: 99%
“…15 Além disso, raramente, as lesões cutâneas podem estar restritas a determinadas áreas corporais segmentares, representando casos de mosaicismo da doença. 32 Quer a mastocitose cutânea difusa, quer o mastocitoma cutâneo, constituem formas praticamente inexistentes na idade adulta. Quando observadas, exibem caraterísticas clínicas semelhantes às observadas na infância.…”
Section: Mastocitoma Cutâneounclassified